Prevention and Management of Post-Endoscopic Retrograde Cholangiopancreatography Complications - Kahaleh, Michel (The Korean Society of Gastrointestinal Endoscopy, 2012)
Endoscopic retrograde cholangiopancreatography (ERCP) is associated with a spectrum of complications such as pancreatitis, hemorrhage, perforation, and cardiopulmonary events. These complications can range from mild to severe resulting in extended hospitalization, requiring surgical intervention, and leading to permanent disability or even death. Complications of ERCP have been better understood in the past decade, with adoption of standardized consensus-based definitions of complications and introduction of new recommendations to minimize risks of ERCP. Adequate selection of patients undergoing ERCP, skilled operators using novel techniques and prompt identification and treatment are key to successful prevention and management.